2022
DOI: 10.1038/s42003-022-03841-8
|View full text |Cite|
|
Sign up to set email alerts
|

Hydroxychloroquine blocks SARS-CoV-2 entry into the endocytic pathway in mammalian cell culture

Abstract: Hydroxychloroquine (HCQ), a drug used to treat lupus and malaria, was proposed as a treatment for SARS-coronavirus-2 (SARS-CoV-2) infection, albeit with controversy. In vitro, HCQ effectively inhibits viral entry, but its use in the clinic has been hampered by conflicting results. A better understanding of HCQ’s mechanism of actions in vitro is needed. Recently, anesthetics were shown to disrupt ordered clusters of monosialotetrahexosylganglioside1 (GM1) lipid. These same lipid clusters recruit the SARS-CoV-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 92 publications
1
37
0
Order By: Relevance
“…We previously showed the cholesterol released from astrocytes requires apoE 17 . We have also showed that purified apoE3 and 10% fetal bovine serum (FBS, an external source of cholesterol) can recapitulate the effects of high extracellular cholesterol 17,21,22 . To confirm microglia activation by apoE-mediated cholesterol uptake, we cultured HMC3 cells with apoE3 with/without FBS and measured TNFα production using an enzymelinked immunosorbent assay (ELISA) for TNFα.…”
Section: Cholesterol Activation Of Microglia and Macrophagesmentioning
confidence: 83%
See 1 more Smart Citation
“…We previously showed the cholesterol released from astrocytes requires apoE 17 . We have also showed that purified apoE3 and 10% fetal bovine serum (FBS, an external source of cholesterol) can recapitulate the effects of high extracellular cholesterol 17,21,22 . To confirm microglia activation by apoE-mediated cholesterol uptake, we cultured HMC3 cells with apoE3 with/without FBS and measured TNFα production using an enzymelinked immunosorbent assay (ELISA) for TNFα.…”
Section: Cholesterol Activation Of Microglia and Macrophagesmentioning
confidence: 83%
“…And studies on cultured cells will need to consider high and low cholesterol environments. In order to recapitulate a disease state, cholesterol will likely need to be elevated 21,22 . Lastly, if the cytokines generated from microglia have access to the same astrocytes that produce their cholesterol, the process would be autocatalytic and produce a chain reaction that would escalate neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated cholesterol is a key cellular component important to many metabolic and neurological diseases, including Alzheimer’s, cardio-vasculature, diabetes, viral infections, and chronic inflammation [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. A gap in understanding exists for how cholesterol affects many diverse biological functions.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphatidylinositol 4,5 bisphosphate (PIP 2 ) is also a membrane-signaling lipid [ 14 , 15 , 16 , 17 , 18 ], and forms charged clusters separate from GM1-containing clusters [ 19 , 20 , 21 , 22 , 23 ] ( Figure 1 A). The distance between GM1 and PIP 2 clusters ranges from 42 nm in muscle cells [ 22 ] to ~200 nm in lung and kidney cells [ 7 ]. PIP 2 clusters are largely insensitive to cholesterol [ 19 , 20 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation